Comparative study of human monocyte and platelet adhesion to hydrogels in vitro - effect of polymer structure - Jiroušková, Markéta; Bartůňková, Jiřina; Smetana, Karel; Lukáš, Jan; Vacík, Jiří; Dyr, Jan Evangelista (Journal of materials science. Materials in medicine, 1997)
Blood platelet and monocyte adhesion was studied in vitro with respect to the influence of hydrophilic polymer chemical functional groups and their charge. The results showed that the strongest adhesion of human monocytes was to coverslips covered with cationic polymer. Platelet adhesion to all tested polymers proved to be negligible; no differences related to the charge of the polymers used were observed. These results show the obvious difference between the biocompatibility and haemocompatibility in vitro which must be taken into consideration during polymer biological properties testing before clinical trials.
Keywords: techniky in vitro; monocyty; In Vitro Techniques; lidé; polymery; Monocytes; adhezivita trombocytů; Polymers; Hydrogels; Platelet Adhesiveness; Humans; hydrogely